Analisis Kadar Glukomanan Dari Biji Durian (Durio zeibethinus Murr) dengan Metode Spektrofotometri pada Berbagai Waktu dan Suhu Hidrolisis: Analysis of Glucomannan Content From Durian Seeds (Durio zeibethinus Murr) Using Spectrophotometry Methods in Several Hydrolysis Times and Temperatures - Darmawati Darmawati; Syaiful Bahri; Husain Sosidi (KOVALEN: Jurnal Riset Kimia, 2020)
Durian seeds are one type of seed that contains glucomannan. The aim is to determine glucomannan levels in the durian seed. The study was designed using a completely randomized design (CRD). The extracted glucomannan was determined by the spectrophotometry method at various temperature and hydrolysis time. The crude extract of glucomannan was hydrolyzed using 3 M HCl for 70, 80, 90, 100, and 110 minutes at 70, 80, 90, 100, and 110°C. The highest glucomannan concentration of 39.60% was obtained at a hydrolysis temperature of 100°C for 100 minutes. The analysis of the FTIR spectrophotometer shown that the vibration of the C-O-C functional group (glycoside bond) was obtained at the wavelength number of 1020.34 cm-1 which is a characteristic of glucomannan. Keywords: glucomannan, durian seed, hydrolysis, spectrophotometry